The transcription factor FLI1 promotes cancer progression by affecting cell cycle regulation. Issue 1 (7th January 2020) - Miao, Beiping; Bauer, Andrea S.; Hufnagel, Katrin; Wu, Yenan; Trajkovic‐Arsic, Marija; Pirona, Anna C.; Giese, Nathalia; Taipale, Jussi; Siveke, Jens T.; Hoheisel, Jörg D.; Lueong, Smiths
Abstract : Binding of transcription factors to mutated DNA sequences is a likely regulator of cancer progression. Noncoding regulatory mutations such as those on the core promoter of the gene encoding human telomerase reverse transcriptase have been shown to affect gene expression in cancer. Using a protein microarray of 667 transcription factor DNA‐binding domains and subsequent functional assays, we looked for transcription factors that preferentially bind the mutant h TERT promoter and characterized their downstream effects. One of them, friend leukemia integration 1 (FLI1), which belongs to the E26 transforming‐specific family of transcription factors, exhibited particularly strong effects with respect to regulating h TERT expression, while the even better binding ELK3 did not. Depletion of FLI1 decreased expression of the genes for cyclin D1 ( CCND1 ) and E2F transcription factor 2 ( E2F2 ) resulting in a G1/S cell cycle arrest and in consequence a reduction of cell proliferation. FLI1 also affected CMTM7, another gene involved in G1/S transition, although by another process that suggests a balanced regulation of the tumor suppressor gene's activity via opposing regulation processes. FLI1 expression was found upregulated and correlated with an increase in CCND1 expression in pancreatic cancer and brain tumors. In non‐neoplastic lung cells, however, FLI1 depletion led to rapid progression through the cell cycle. This coincides with the fact that FLI1 is downregulated in lung tumors. Taken together, our data indicate a cell cycle regulatory hub involving FLI1, h TERT, CCND1 and E2F2 in a tissue‐ and context‐dependent manner. Abstract : What's new? Noncoding regulatory mutations on the core promoter of human telomerase reverse transcriptase (h TERT ) have been shown to affect gene expression in cancer. Using a protein microarray of 667 transcription factor DNA‐binding domains and subsequent functional assays, the authors identified an ETS transcription factor family member – FLI1 – that binds preferentially to mutated, cancer‐associated h TERT promoters, thereby modulating cell cycle progression through regulation of the G1/S transition. FLI1 could exert both oncogenic and tumor suppressive roles in a tissue‐specific manner. Taken together, the data indicate a cell cycle regulatory hub involving FLI1, h TERT, CCND1, and E2F2 in a tissue‐ and context‐dependent manner.